SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84344-ms
|View full text |Cite
|
Sign up to set email alerts
|

Role of Convective Mixing in the Long-Term Storage of Carbon Dioxide in Deep Saline Formations

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractStorage of carbon dioxide in deep formations is being actively considered for the reduction of greenhouse gas emissions. Relevant experience in the petroleum industry comes from natural gas storage and enhanced recovery using carbon dioxide, but this experience is over a time scale less than the hundreds or thousands of years required for carbon dioxide storage. On these long time scales different mechanisms need to be considered.In the long-term the dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 66 publications
(70 reference statements)
3
128
0
Order By: Relevance
“…Trapping occurs primarily after injection, when the CO 2 migrates due to the aquifer slope and the natural head gradient. As the buoyant plume of mobile CO 2 (dark gray) rises and spreads away from the well array, residual trapping immobilizes blobs of CO 2 in its wake (light gray) (19,29,30), and solubility trapping shrinks the plume from below (blue) (20,21). and opposite slope until returning to the current rate (Fig.…”
Section: Storage Demand Vs Supply Dictates Ccs Lifetimementioning
confidence: 99%
See 1 more Smart Citation
“…Trapping occurs primarily after injection, when the CO 2 migrates due to the aquifer slope and the natural head gradient. As the buoyant plume of mobile CO 2 (dark gray) rises and spreads away from the well array, residual trapping immobilizes blobs of CO 2 in its wake (light gray) (19,29,30), and solubility trapping shrinks the plume from below (blue) (20,21). and opposite slope until returning to the current rate (Fig.…”
Section: Storage Demand Vs Supply Dictates Ccs Lifetimementioning
confidence: 99%
“…Although trapping can be analyzed over a wide range of length scales, we consider trapping at the large scale of an entire geologic basin because large volumes of CO 2 will need to be stored to offset emissions (3). We consider residual trapping, in which blobs of CO 2 become immobilized by capillary forces (19), and solubility trapping, in which CO 2 dissolves into the groundwater (20,21), because these mechanisms operate over relatively short timescales and provide secure forms of storage ( Fig. 1 A and B).…”
mentioning
confidence: 99%
“…The CO 2 -enriched brine has a slightly higher density than the original brine (Ennis-King and Paterson 2005, Moortgat et al 2011). This leads to gravitational flow instabilities in the reservoir (Riaz et al 2006, Pau et al 2010, and it is believed that the CO 2 -rich brine sinks in the reservoir over hundreds to millions of years (Bachu 2000, Ennis-King and Paterson 2005, Lindeberg and Wessel-Berg 1997 in the form of thick and thin fingers (cp. Figures 1 and 2), however this is an active area of research and it has been suggested that this mechanism is considerably faster (Moortgat et al 2011).…”
Section: Reservoir Fluid Dynamicsmentioning
confidence: 99%
“…In fact, CO 2 -saturated brine is denser than native brine. As CO 2 -laden brine sinks deeper into the formation, it can set up circulation patterns that enable more free-phase CO 2 to come into contact with native brine, enabling more dissolution to occur (Ennis-King and Paterson 2005;Pruess and Zhang 2008). (4) Mineral trapping: CO 2 reacts with rock minerals to form carbonate compounds, typically over very long time scales Xu et al 2003Xu et al , 2005Gherardi et al 2007).…”
Section: Fig 1 Map Of California Showing Potential Geologic Carbon Smentioning
confidence: 99%